Strategy Analysis Of Batik Home Industry Development - Ika ‘Asaliatun Amalia; M. Trihudiyatmanto (Jamasy: Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2022)
This study aims to determine the right business development strategy by first identifying and assessing the company's internal and external factors to analyze the application of the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) which was coined by Albert Humphrey. This study uses OCAI analysis (Organizational Culture Assessment Instrument) to know the cultural condition of Home Industry Batik Prupuk Kalibeber Wonosobo. This research is a type of qualitative descriptive research, namely research that explains something that is the target of research in detail or in depth. The object of this research is Home Industry Batik Prupuk Kalibeber Wonosobo. The subjects or samples of this research are the owners and employees of the Home Industry Batik Prupuk Kalibeber Wonosobo, the technique used is non-probability sampling, namely judgment sampling. The results showed that based on the analysis of IFAS a total score of 2.46 and EFAS a total score of 2.34 which indicates that the company's current position is in quadrant I (aggressive). Based on the results of the OCAI analysis, it shows that the current state of corporate culture isadhocracy culture with the highest value of 25.83.